INOVASI DESAIN PRODUK UMKM: APLIKASI SCAMPER DI KELAS STUDIO DESAIN PRODUK - Nurrul Haq, Bayyinah (Jurnal Muara Pendidikan, 2024)
Collaboration between higher education institutions and industry in learning activities can strengthen their roles in enhancing industrial competitiveness, such as through partnerships between MSMEs in the creative sector and design programs for product innovation. Product design is a key factor in boosting product competitiveness. This study discusses implementing the SCAMPER technique as an idea development method in the Product Design Studio 4 course at Trilogy University. This course adopts a Project Based Learning approach involving MSMEs as partners, where students act as "in-house designers". Using a qualitative approach involving 12 students, SCAMPER was applied in weeks 10-12 out of the 16-week course, specifically during the concept development and design description phase. The research findings indicate that students were able to apply 3 or more sub-techniques within SCAMPER for their projects, with Modify, Adapt, and Combine being the most frequently utilized sub-techniques. The Re-Arrange/Reverse sub-technique was not employed as the design project focused on enhancing existing products within MSMEs. Variances in students' capabilities and project complexities necessitate structured guidance and flexible class planning to ensure a collaborative and effective creative process.